1993
DOI: 10.1021/bi00069a024
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and processivity of ATP hydrolysis and DNA unwinding by the RecBC enzyme from Escherichia coli

Abstract: The RecB and RecC subunits of the RecBCD enzyme from Escherichia coli were purified from cells containing plasmids overproducing these proteins [Boehmer, P.E., & Emmerson, P.T. (1991) Gene 102, 1-6]. RecB hydrolyzes ATP in the presence of either single- or double-stranded DNA. RecC stimulates ATP hydrolysis by RecB, particularly with double-stranded DNA. The steady-state kinetic parameters for ATP hydrolysis by RecBC with double-stranded DNA are kcat = 1600 min-1, Km = 8.1 microM, and kcat/Km(ATP) = 1.97 x 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 28 publications
(58 reference statements)
4
63
0
Order By: Relevance
“…However, RecD is dispensable for unwinding, since RecBC enzyme is also a helicase (41,42), and the major effect of removing RecD from RecBCD is on the nuclease activity of RecBCD. Loss of the RecD subunit reduces the nuclease activity to very low levels that are not biologically relevant (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, RecD is dispensable for unwinding, since RecBC enzyme is also a helicase (41,42), and the major effect of removing RecD from RecBCD is on the nuclease activity of RecBCD. Loss of the RecD subunit reduces the nuclease activity to very low levels that are not biologically relevant (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…This model is supported by the fact that recD mutants are recombination-proficient (11,23,29) and hyperre-combination-proficient in the absence of Chi sites (11), and they cluster recombination events at the ends of DNA in lambda replication-blocked crosses (30). Purified RecBC enzyme (i.e., lacking RecD) has a low affinity for dsDNA (unpublished data, see Table 5) ends but can unwind DNA (16,31,32) and facilitates loading of RecA protein at the 3Ј termini of DNA during unwinding (16). This is in contrast to RecBCD enzyme, which requires a Chi site for significant loading of RecA protein (6), joint molecule formation (7), and recombination (18).…”
mentioning
confidence: 98%
“…The RecBC enzyme (without the RecD subunit) is a very processive helicase but has no significant nuclease activity (16,22,23). Recently, it was shown that the RecBC enzyme also coordinates the loading of RecA protein and that this loading is independent of .…”
mentioning
confidence: 99%
“…Ϫ1 cm Ϫ1 at 280 nm, derived by adding the respective extinction coefficients for the individual subunits (23). No contaminating protein bands were detected when 1 g of protein was loaded on an SDS-polyacrylamide gel and stained with Coomassie Brilliant Blue.…”
mentioning
confidence: 99%